2017
DOI: 10.12657/denbio.077.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Italian populationsof Abies alba

Abstract: Silver fir (Abies alba) is a common tree species in the mountainous areas in Europe. A number of natural stands in the hilly regions of northern Europe represent relic populations. The aim of the research was to evaluate the diversity present in Italian populations of the species. Genetic diversity was assessed in 45 silver fir populations covering the species' distribution range in Italy, based on the allelic variation present at seven microsatellite loci (SSRs). A consistent level of intra-population variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
15
2
Order By: Relevance
“…Nuclear microsatellites have been extensively employed in studying genetic variation of coniferous tree species [12,[43][44][45][46]. In the present study, genetic variation within and between populations and their genetic structure were analyzed in five natural populations of Norway spruce from Serbia, using eight EST-SSR markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear microsatellites have been extensively employed in studying genetic variation of coniferous tree species [12,[43][44][45][46]. In the present study, genetic variation within and between populations and their genetic structure were analyzed in five natural populations of Norway spruce from Serbia, using eight EST-SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of genetic diversity pattern at intra-and inter-population levels is a fundamental requirement for the establishment of programs aimed at conservation of forest genetic resources [12]. Population genetic diversity has a substantial effect on both individual fitness and population adaptive capacity [13], thereby playing a vital role in ensuring species capability to withstand various biotic and abiotic stressors and evolve under altered environmental conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pieces of evidence of common haplotypes, which grouped Italian and Balkan populations, were also found in Turkey oak (Quercus cerris; Bagnoli et al, 2016). Similarly, studies on silver fir (Abies alba) in the Apennines and Balkans found genetic similarity between the southern Apennines and eastern European populations (Belletti et al, 2016;Piotti et al, 2017). These studies are in agreement with ours and point toward the existence of historical gene flow between southern Italy and the Balkan peninsula (Carabeo et al, 2016), when the Apennine and Balkan Peninsulas were connected during Pleistocene at glaciation periods and concomitant sea-level drops (Nieto Feliner, 2014).…”
Section: Population Structure and Gene Flowmentioning
confidence: 85%
“…The genus Abies of the Pinaceae family consists approximately of 50 species, which are largely distributed in temperate and boreal regions of North and Central America, Europe, Asia, and North Africa, eight of which are endemic to the Mediterranean region [13]. The silver fir (Abies Alba Mill.)…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, silver fir covers an area of about 68,000 ha, being relatively common in the central and eastern parts of the Alps, while its populations in the Apennines are fragmented, although large stands are found [13]. Evidence has been shown that the present northern Apennines silver fir populations are relicts of past large populations, as well as that these populations are characterized by a genetics distinct from relatively nearby alpine populations, leading to specific recommendations for their conservation and enrichment [14].…”
Section: Introductionmentioning
confidence: 99%